170k views
2 votes
2x − y = -2

3y = 6 − 5x



x = 0, y = 2

x = 2, y = 0

x = 2, y = 2

x = 0, y = -2

2 Answers

7 votes
you can use the substitution method to solve this

2x - y = -2 (change this to be y = 2x + 2 and substitute it for y value)
3y = 6 - 5x
3(2x + 2) = 6 - 5x use distributive property
6x + 6 = 6 - 5x add 5x to both sides
11x + 6 = 6
x = 0 substitute this into an original equation and solve for y

3y = 6 - 5x
3y = 6 - 5(0)
3y = 6
y = 2 (0, 2) answer x=0 y= 2
User Omoro
by
6.2k points
2 votes
If you're asking which is correct, the answer is the first one: x = 0 and y = 2. You figure this out by substituting in the values and seeing that they are correct, so:
(2 × 0) - 2 = -2
0 - 2 = -2
(3 × 2) = 6 - (5 × 0)
6 = 6 - 0
I hope this helps!
User Terma
by
5.7k points